KOMUNIKASI SEBAGAI PEMODERASI PENGARUH PARTISIPASI TERHADAP KEPUASAN DALAM PENGEMBANGAN SISTEM - Widiastiti, Ida Ayu Komang; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2016)
ABSTRACT   The purposes of this research  are to examine the effect of user participation to user satisfaction and user-developer communication skills in moderating influence on user satisfaction user participation in the development of information systems. This research was conducted at the Office of Denpasar government that has made the development of an information system in 2010-2014. Sampling of this research is the method of non-probability sampling with purposive sampling technique. Data were collected using survey method with interviews and questionnaires. Respondents of this study as many as 71 people. The data analysis technique used is the test Moderating Regression Analysis (MRA). Overall variable in this study is valid and reliable. The research data qualifies that the normal distribution of data and models used do not contain any heteroscedasticity. The first hypothesis testing results prove that the variable user participation is positive and significant impact on user satisfaction. Results of testing the second hypothesis results that the user-developer communication variable does not moderate the effect of user participation to user satisfaction.
Keywords: Keywords: User Participation, User Satisfaction, Communication User-Developer, Information Systems Development.